YES Problem: a(a(b(b(b(b(a(a(x1)))))))) -> a(a(c(c(a(a(b(b(x1)))))))) a(a(c(c(x1)))) -> c(c(c(c(a(a(x1)))))) c(c(c(c(c(c(x1)))))) -> b(b(c(c(b(b(x1)))))) Proof: String Reversal Processor: a(a(b(b(b(b(a(a(x1)))))))) -> b(b(a(a(c(c(a(a(x1)))))))) c(c(a(a(x1)))) -> a(a(c(c(c(c(x1)))))) c(c(c(c(c(c(x1)))))) -> b(b(c(c(b(b(x1)))))) Matrix Interpretation Processor: dim=4 interpretation: [1 0 0 0] [0 0 0 0] [c](x0) = [0 0 1 0]x0 [0 0 0 0] , [1 0 0 0] [0 1 1 0] [b](x0) = [0 0 0 0]x0 [0 0 0 0] , [1 0 0 1] [0] [0 1 0 0] [0] [a](x0) = [1 0 0 0]x0 + [1] [0 1 0 0] [0] orientation: [2 2 0 2] [1] [1 1 0 1] [0] [1 1 0 1] [1] [1 1 0 1] [1] a(a(b(b(b(b(a(a(x1)))))))) = [1 1 0 1]x1 + [1] >= [0 0 0 0]x1 + [0] = b(b(a(a(c(c(a(a(x1)))))))) [1 1 0 1] [1] [0 0 0 0] [0] [1 1 0 1] [0] [1 0 0 0] [0] [0 0 0 0] [0] [0 0 0 0] [0] c(c(a(a(x1)))) = [1 0 0 1]x1 + [1] >= [1 0 0 0]x1 + [1] = a(a(c(c(c(c(x1)))))) [0 0 0 0] [0] [0 0 0 0] [0] [1 0 0 0] [1 0 0 0] [0 0 0 0] [0 0 0 0] c(c(c(c(c(c(x1)))))) = [0 0 1 0]x1 >= [0 0 0 0]x1 = b(b(c(c(b(b(x1)))))) [0 0 0 0] [0 0 0 0] problem: c(c(a(a(x1)))) -> a(a(c(c(c(c(x1)))))) c(c(c(c(c(c(x1)))))) -> b(b(c(c(b(b(x1)))))) String Reversal Processor: a(a(c(c(x1)))) -> c(c(c(c(a(a(x1)))))) c(c(c(c(c(c(x1)))))) -> b(b(c(c(b(b(x1)))))) Matrix Interpretation Processor: dim=1 interpretation: [c](x0) = x0 + 1, [b](x0) = x0, [a](x0) = 2x0 + 1 orientation: a(a(c(c(x1)))) = 4x1 + 11 >= 4x1 + 7 = c(c(c(c(a(a(x1)))))) c(c(c(c(c(c(x1)))))) = x1 + 6 >= x1 + 2 = b(b(c(c(b(b(x1)))))) problem: Qed